Surface Roughness and Hardness of CAD/CAM Ceramic Materials after Polishing with a Multipurpose Polishing Kit: An In Vitro Study - Limpuangthip, Nareudee; Poosanthanasarn, Ekaluck; Salimee, Prarom (European Journal of Dentistry, 2022)
Objective This article evaluates the effect of multipurpose polishing kit on surface roughness and hardness of three computer-aided design/computer-aided manufacturing (CAD/CAM) ceramic materials at different polishing durations. Weight changes of the polishing bur were also determined.Material and Methods Three CAD/CAM ceramic materials were lithium disilicate glass ceramic (IPS e.max CAD), translucent zirconia (VITA YZ), and zirconia-reinforced lithium disilicate ceramic (Celtra Duo). Ceramics were ground with a diamond bur, and polished with the multipurpose polishing kit (Eve Diacera HP), which comprises coarse and fine polishing burs. Surface roughness value (Ra) was measured using a noncontact optical profilometer (n = 10 per group) after grinding and every 15 seconds of coarse and fine polishing until 60 seconds. The complete polishing Ra was compared with the lab as-received specimens and human enamel. Surface morphology was examined using a scanning electron microscope after 60-second coarse and fine polishing and compared with the lab as-received specimens. Hardness was measured using a Vickers hardness tester on the lab as-received specimens and after the final polishing process (n = 4 per group). Changes in surface roughness and polishing bur weight of each material were analyzed using one-way repeated-measures analysis of variance (ANOVA) and dependent t-test. One-way ANOVA was used to detect differences in surface roughness, Vickers hardness, and bur weight among materials within the same polishing duration (α = 0.05).Results From grinding to complete polishing, the greatest Ra reduction was found in VITA YZ, followed by Celtra Duo and IPS e.max CAD. Final Ra values of all ceramics after 60-second fine polishing were not significantly different, and were similar to that of enamel and lab as-received specimens. Vickers hardness of ceramic materials did not change after grinding and polishing. Coarse polishing bur demonstrated the highest weight loss after polishing VITA YZ, followed by Celtra Duo and IPS e.max CAD.Conclusion The multipurpose polishing kit reduced surface roughness of CAD/CAM ceramic materials to the similar level of the lab as-received specimen and enamel regardless of material's hardness. The reductions of surface roughness and a coarse polishing bur weight were highest in VITA YZ, followed by Celtra Duo and IPS e.max CAD.
Keywords: CAD/CAM materials; glass ceramic; lithium disilicate; polishing bur; zirconia